Odpowiedzi

2010-03-22T16:08:11+01:00
A) 5 *(-3)² - 2 * (-3) = -15 +6 = -9
b) 12(-3 + 0,4) - 0,4 * (-3) = 12* (-2,6) + 1,2 = - 31,2 + 1,2 = 32,4
c) (-3)² + 2 (-3+3) 9 + 2 * 0 9
______________= _______ = _____ =1,29
(-3)² - 2 9 - 2 7
d) 2 + 5(-3) 2 -15 -13
__________= _______= ______= -2,6
2 - (-3) 2 + 3 5
2010-03-22T16:08:42+01:00
a) 5 x² - 2x

5*(-3)2 -2(-3)= 5*9-2+3=46

b) 12 (x + 0,4) - 0,4 x
12(-3+0,4) +1,2=-36+4,8+1,2=-30

c) x² + 2 (x+3)
─────── = 9-6+6 = 9 = 1 i 2/7
x² - 2 ... .. 9-2 ....7

d) 2+5x
─── = 2+ 5 (-3) = 2- 15 = -13 = - 2 i 3/5
2-x ....... 2+3 ...... 5 .... 5